Drilled Pile Design and Installation Challenges in an Urban Environment - Luis Berroteran; Satyajit Vaidya; Rudolph Frizzi (Deep Foundations Institute, 2018)
This paper presents design and construction challenges associated with a high-capacity rock-socketed drilled pile foundation system for a 60-story building recently constructed in an urban environment. The site is in very close proximity to surrounding 1-to-6-story buildings and a commuter rail subway tunnel structure. High compression, uplift, and lateral loads imposed by the tall, slender tower constructed over a relatively small site footprint posed a significant design challenge due to the close proximity of the subway tunnel and other structures. Construction challenges included those associated with advancing the drilled pile casings through overburden materials using internal flush method mandated by the Transit Agency, advancing the casings through very dense glacial till materials encountered above top of rock, and drilling rock sockets in variable rock conditions. This paper provides a brief overview of the site and subsurface conditions, and discusses the resulting design and construction challenges for the drilled pile foundation system and how they were addressed. SITE AND SUBSURFACE CONDITIONS The 8,350-square-foot site is located in a busy neighborhood in downtown New York City (NYC). Buildings neighboring the site are supported on shallow foundations, and their basements extend about 15 feet below the sidewalk level. A NYC-Landmarked building is located within a NYC Department of Buildings (DOB)-designated 90-foot influence limit from the Project site. NYC Transit Authority (NYCTA) subway tunnel and station structures are located in close proximity to the Project site. The subway tunnel structure extends about 50 to 55 feet below the sidewalk level. Although the upper portion of the tunnel structure is about 13.5 feet away from the site property line, the lower portion is only about 1 foot away from the property line. A site location plan is presented as Fig. 1. Geotechnical borings revealed subsurface conditions generally consisting of successive strata of surficial fill, sandy and silty soils, and glacial till (predominantly consisting of cobbles and boulders) overlying mica schist bedrock. A generalized subsurface profile is presented in Fig. 2. The surficial fill stratum was about 10 to 23 feet thick, and generally consisted of loose to medium dense sandy soils with varying proportions of silt, gravel, and miscellaneous debris such as brick. The underlying sandy and silty soil stratum was about 60 to 79 feet thick and generally consisted of loose to medium dense inter-bedded layers of fine to coarse sand, silty fine sand, and silt. The underlying glacial till stratum was about 26 to 70 feet thick and generally consisted of cobbles and boulders embedded in a very dense soil matrix. Top of bedrock was encountered in the borings about 110 to 150 feet below sidewalk level. Groundwater level was measured at about 30 feet below sidewalk level.